Health professionals' practice for young people with, or at risk of, Li–Fraumeni syndrome: An Australasian survey. Issue 5 (23rd December 2019) - Forbes Shepherd, Rowan; Keogh, Louise A.; Werner‐Lin, Allison; Delatycki, Martin B.; Forrest, Laura E.
Abstract: Li–Fraumeni syndrome (LFS), a rare cancer syndrome caused by pathogenic germline variants in TP53, has serious implications for adolescents and young adults (AYAs; aged 15–39 years). The early‐onset and multi‐organ cancer risk associated with LFS means health professionals must concurrently contend with the developmental needs of individuals who are diagnosed from a young age, and recent changes in practice due to advances in whole‐body cancer surveillance. To help understand how current practice meets the developmental needs of AYAs with, or at risk of, LFS, we conducted a national online survey to explore the experiences of health professionals who care for this population in Australia and New Zealand. Forty‐three respondents completed the survey (56% genetic counselors), one‐third of whom had facilitated predictive TP53 testing for minors ( n  = 14/43, 33%). In hypothetical scenarios describing 15‐year‐olds eligible for predictive TP53 testing, respondents were more supportive of testing for emotionally mature compared to immature minors ( p  = .009); and more supportive of adolescent wishes compared to parental wishes for testing ( p  = .020) when families held discordant views on testing. Genetic health professionals were more likely than oncology health professionals to address psychological ( p  = .017) and information needs about reproductive options for LFS during consultations than to refer them on ( p  = .004). All respondents supported comprehensive risk management for LFS, but noted important medical, logistical, and psychosocial limitations for AYAs. This study offers valuable insight into developmentally appropriate practices of Australasian health professionals who care for AYAs with, or at risk of, LFS. These findings suggest they may foster the autonomy of minors undergoing predictive TP53 genetic testing and be supportive of new whole‐body risk management guidelines.